Документи ЦДАМЛМ України про видатну актрису театру і кіно XX ст. Наталію Ужвій - Кирилюк, Г. (Архіви України, 2008)
The article deals with the documents of the personal archives of Nataliia Yzhviy, a prominent theatre and cinema actress of XX century, which is preserved at TsDALM of Ukraine.